Hipopara-Red, Real Life Experience in 322 Patients with Hypoparathyroidism - Zanchetta, María Belén (2020)
Context:Hypoparathyroidism is a rare disease and as such, its natural history, long term complications and correct clinical management remain unclear.ObjectiveTo describe the natural history and clinical characteristics of the disease.Design and settingTopresent a retrospective observational analysis from seven specialized centers in Buenos Aires, Argentina.Patientschronic hypoparathyroid patients followed up between 1985 and December 2018.Main Outcome Measuresdata on demographics, etiology, clinical complications, biochemical parameters, DXA values and treatment doses were collected.Results322 subjects with chronic hypoparathyroidism were included, 85.7 % were female. Mean age was 55.2 ± 16.8 years and mean age at diagnosis was 43.8 ± 16.8. Prevalence of surgical hypoparathyroidism was 90.7 %, most common causes being thyroid carcinoma and benign thyroid disease. A history of hypocalcemia requiring hospitalization was present in 25.7 % and 4.3 % had a history of seizures. Overall, 40.9 % had reported at least one neuromuscular symptom. Renal insufficiency was present in 22.4 % and was significantly associated with age (p<0.0001). Hyperphosphatemia was present in 42 %. A history of severe hypocalcemia, paresthesias, tetany, ganglia calcifications, seizures and cataracts was significantly higher in nonsurgical patients.ConclusionAlthough these patients were followed up by experienced physicians, clinical management was heterogeneous and probably insufficient to assess all the potential complications of this chronic disease. Almost 70 % of this group of patients met the experts´ indications for considering the use of rhPTH 1-84. Being aware of this fact is the first step to improve our medical management of this disease in the future.